2019
DOI: 10.1002/art.40737
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Treg Cell Therapy in a Patient With Systemic Lupus Erythematosus

Abstract: Objective Adoptive Treg cell therapy has great potential to treat autoimmune disease. Currently, very little is known about how these cells impact inflamed tissues. This study was undertaken to elucidate how autologous Treg cell therapy influences tissue inflammation in human autoimmune disease. Methods We describe a systemic lupus erythematosus (SLE) patient with active skin disease who received adoptive Treg therapy. We comprehensively quantified Treg cells and immune activation in peripheral blood and skin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 24 publications
(39 reference statements)
3
83
0
1
Order By: Relevance
“…By comparison, autologous T regs have been detected in circulation for up to 1 year post‐transfer using mass spectrometry. However, similar to findings with allogeneic cells, using a flow cytometry‐based read‐out the percentage of T regs in circulation peaked 7–14 days post‐transfer and fell near the detection limit within 3 months. Thus, more work is required to understand why the majority of infused T regs seem to disappear from the circulation in these different contexts.…”
Section: Sources Of Tregssupporting
confidence: 71%
See 2 more Smart Citations
“…By comparison, autologous T regs have been detected in circulation for up to 1 year post‐transfer using mass spectrometry. However, similar to findings with allogeneic cells, using a flow cytometry‐based read‐out the percentage of T regs in circulation peaked 7–14 days post‐transfer and fell near the detection limit within 3 months. Thus, more work is required to understand why the majority of infused T regs seem to disappear from the circulation in these different contexts.…”
Section: Sources Of Tregssupporting
confidence: 71%
“…For example, groups using magnetic selection to isolate T regs from peripheral blood deplete CD8 + cells , whereas groups isolating T regs from UCB do not . Groups with access to flow cytometric sorting capability typically include additional markers such as positive selection for CD45RA or negative selection for CD127 . Inclusion of CD45RA or CD127 in the selection strategy increases the purity of the resulting cells compared to those isolated using magnetic selection, as these markers remove most of the CD25 + activated T cells that are primarily CD45RO + CD45RA – and CD127 pos .…”
Section: Treg Cell Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, terminally differentiated cells fulfill opposite functions: Th17 cells cause autoimmunity and inflammation, whereas Treg cells inhibit these phenomena and maintain immune homeostasis (1,2). Emerging studies about patients and experimental models have determined the imbalance between Th17 and Treg cells as well as the related cytokines in the serum, including IL-6, IL-1b, and IL-23, and signal transducer, participated in the onset and progression of autoimmune diseases including SLE (3,27), immune therapy could restore Treg/Th17 imbalance and thus ameliorate SLE and RA (4,8,(28)(29)(30). Considering of the important immune regulatory effect of stem cells on Treg/Th17 (8,15,31), the imbalance between Treg and Th17 cells might be associated with SLE BM-MSC dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluating the efficacy of low-dose IL-2 treatment in patients with SLE found an increase in the number of Treg cells and suppression of follicular helper T cells and Th17 cell numbers in peripheral blood, accompanied by a marked reduction in disease activity [66]. A recent intriguing report described the first case of a patient with SLE treated with autologous adoptive Treg cell therapy, which led to increased activated Treg cells in the inflamed skin, with a marked attenuation of the IFN-γ pathway and a reciprocal augmentation of the IL-17 pathway [67]. This phenomenon was more pronounced in skin than in peripheral blood and was validated in a mouse model undergoing Treg cell adoptive transfer.…”
Section: Discussionmentioning
confidence: 99%